2021
DOI: 10.3390/bs11050069
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Sleep and Poor Sleep Quality Completely Mediate the Relationship between Financial Stress and Dietary Risk among Higher Education Students

Abstract: The coronavirus disease 2019 (COVID-19) pandemic worsened financial stress for higher education students in the U.S. Financial stress is associated with poor dietary behaviors; however, factors that might influence this relationship are not well characterized. The present cross-sectional study investigated the associations between financial stress and dietary intake and dietary risk scores among higher education students (undergraduate and graduate students) in the U.S. and examined whether poor sleep quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 84 publications
1
10
0
1
Order By: Relevance
“…Ghanaian students reported financial stress scores of 15.6 ± 4.9. A recent study of higher education students in the United States during the COVID-19 pandemic reported financial stress scores of 17.4 ± 5.9 ( Du et al, 2021a ), or roughly 10% higher. A previous study that conducted focus group discussions about academic stress with Ghanaian undergraduate students noted that many reported financial concerns were a significant source of stress ( Adom and Adu Mensah, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ghanaian students reported financial stress scores of 15.6 ± 4.9. A recent study of higher education students in the United States during the COVID-19 pandemic reported financial stress scores of 17.4 ± 5.9 ( Du et al, 2021a ), or roughly 10% higher. A previous study that conducted focus group discussions about academic stress with Ghanaian undergraduate students noted that many reported financial concerns were a significant source of stress ( Adom and Adu Mensah, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Du ve arkadaşları [96] tarafından yapılan bir araştırmada, yüksek öğrenim gören öğrencilerin günlük meyve tüketim miktarları ile PSQI puanı arasında zıt yönlü ilişki olduğu saptanmıştır. Puan ne kadar yüksek ise uyku kalitesi o kadar bozulmaktadır Bu sonuç, günlük meyve tüketim miktarı artışı ile uyku kalitesinin iyileştiğini göstermektedir.…”
Section: Yılmaz Ve Altunkürekunclassified
“…Poor sleep quality is a crucial public health problem that increases the risk of premature morbidity and mortality ( Stranges et al, 2012 ). Specifically, poor sleep quality can cause a variety of undesirable consequences such as poor academic performance ( Maheshwari and Shaukat, 2019 ), dietary risk ( Du et al, 2021 ), suicidal ideation ( Littlewood et al, 2019 ), and other mental health problems ( Kim et al, 2021 ). Therefore, it is important to identify and characterize the factors that modulate sleep quality and quantity among college students.…”
Section: Introductionmentioning
confidence: 99%